2016
DOI: 10.1371/journal.pone.0149435
|View full text |Cite
|
Sign up to set email alerts
|

MIRU-VNTR Genotyping of Mycobacterium tuberculosis Strains Using QIAxcel Technology: A Multicentre Evaluation Study

Abstract: BackgroundMolecular genotyping of M.tuberculosis is an important laboratory tool in the context of emerging drug resistant TB. The standard 24-loci MIRU-VNTR typing includes PCR amplification followed by the detection and sizing of PCR fragments using capillary electrophoresis on automated sequencers or using agarose gels. The QIAxcel Advanced system might offer a cost-effective medium-throughput alternative.MethodsPerformance characteristics of the QIAxcel Advanced platform for the standard 24 VNTR loci panel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
(37 reference statements)
1
14
0
Order By: Relevance
“…These variations particularly affected loci 2163b and 4052. According to the authors of this study, the accuracy depended primarily on the PCR fragment length being suboptimal for sizes >750 bp [8]. These problems could be both loci-specific and PCR fragment size-dependent, as observed in our study.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…These variations particularly affected loci 2163b and 4052. According to the authors of this study, the accuracy depended primarily on the PCR fragment length being suboptimal for sizes >750 bp [8]. These problems could be both loci-specific and PCR fragment size-dependent, as observed in our study.…”
Section: Discussionsupporting
confidence: 61%
“…The new approach to variable number tandem repeats (VNTR) analysis using the QIAxcel capillary electrophoresis system and a software-integrated peak calling function was first reported in Japan in 2013 [14]. The multicenter study conducted in two references centers in London and Milan [8] compared the QIAxcel genotyping results with the reference technique and demonstrated that PCR fragment sizes varied significantly depending on the number of copies within specific VNTR loci with the shortest and longest fragments. These variations particularly affected loci 2163b and 4052.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These discrepancies could be attributed to the errors in the interpretation of experimental results, microevolution or inaccuracies in the genome assembly. The experimental result is prone to errors due to sub-optimal PCR amplification, which results in multiple bands on an agarose gel electrophoresis and affects the interpretation of experimental results ( Nikolayevskyy et al, 2016 ; Supply, 2005 ). The microevolution could also result in minor discrepancies between the experimental genotyping and WGS.…”
Section: Discussionmentioning
confidence: 99%